Electrical and Thermal Conductivity of Cyclic Natural Rubber/Graphene Nanocomposite Prepared by Solution Mixing Technique - Vivi Purwandari; Saharman Gea; Basuki Wirjosentono; Agus Haryono; I Putu Mahendra; Yasir Arafat Hutapea (Indonesian Journal of Chemistry, 2020)
Thermal and electrical conductivity studies of Cyclic Natural Rubber nanocomposite with graphene 1 and 2 phr (G1 and G2) and modified 1 and 2 graphenes (mG1 and mG2) have been carried out. Graphene was activated with cetrimonium bromide (CTAB), was isolated from Sawahlunto coal (Bb) by the Hummer modification method. The nanocomposite was fabricated through the mixing solution method using Xylena as a solvent. The characterizations of nanocomposites which were performed by Fourier Transform Infrared (FT-IR) and X-Ray Diffraction (XRD) reveals an interaction between graphene, CTAB and the CNR matrix. Furthermore, Scanning Electron Magnetic (SEM) and Transmission Electron Microscopy (TEM) indicate the particle size to be smaller and particle distribution is more in accordance with CTAB. Thermal analysis of nanocomposites using Differential Scanning Calorimeter (DSC) showed an increase in thermal conductivity from 3.0084 W/mK to 3.5569 W/mK. Analysis of electrical conductivity using the Two-Point Probe shows 2 phr mG (mG2) capable of increasing electrical conductivity from 0.1170 × 10–4 S/cm to 0.2994 × 10-4 S/cm.